Desenvolvimento e avaliação de desempenho de um sistema de posicionamento automático para painéis fotovoltaicos - Cagnon, José Angelo [UNESP] (2010)
The need of using electric energy in localities not attended by the utilities, with efficiency, reliability and accessible cost, has motivated the development of this research, which main approach was photovoltaic systems and the search for better performance of these systems with the solar panels positioning toward the sun. This work presents the experimental development of an automatic positioning system for photovoltaic panels and the evaluation of this system's behavior taking in account the increase in generation of electric energy and its costs of implantation. It was designed a simplified electromechanical device, which is able to support and to move a photovoltaic panel all day long and all year long, keeping its surface aimed to the sun rays, without using sensors and with optimization of movements, due to the adjustment of panel's inclination take place only once a day. The obtained results indicated that the proposal is viable, demonstrating better utilization of the solar energy, showing a compatible cost compared to the increase in the generation of electricity.